E-learning in Libyan Universities ... Reality of Use and Obstacles: A Field Study on The Faculties of Humanities and Law at Alasmarya Islamic University - Dihoum, Maryam Ansir; Ben Arous, Iman Hussein Mohammed; Atallah, Amal Belaid; Ishkib, Rokia Khaled (The annual Scientific Conference for Under and Postgraduate Students at the University., 2023)
The study aimed to identify the reality of E-learning in Libyan universities, provide some recommendations that could contribute to the interest in using and adopting this method, and identify the difficulties that may face the application of this advanced academic method. The researchers relied on the descriptive analytical approach, and a questionnaire was designed as a tool. To collect study data from the study population of (73) faculty members, it was distributed to a sample size of (52) individuals. The study data was analyzed and its hypotheses were tested using the statistical program (SPSS). Among the most important results reached by this study were; The use of E-learning contributes significantly to achieving educational goals efficiently. The faculty members of the faculties of Humanities and Law are very proficient in collecting information from its sources well. Developing and regulating the college’s laws and regulations related to the foundations and requirements of E-learning. The study concluded with a number of recommendations related to the need to raise the level of faculty members’ awareness of the concept of E-learning through educational seminars and supportive publications, and providing all the material requirements of modern devices and networks Internet and advanced equipment necessary to use E-learning in the Faculty, in addition to holding training courses and technical workshops for faculty members in the college to develop their skills in line with technological development in the field of E-learning, in addition to requesting the university faculty administrations to provide the necessary financial support to properly implement E-learning in the faculties. Filling administrative positions in faculties with active young people who possess a leadership spirit, and developing and enacting laws and regulations at the college that relate to the foundations and requirements of E-learning.
Keywords: Communication technology; Information technology; Communication networks; E-learning; Traditional education